125k views
0 votes
Please help This is geometry

Please help This is geometry-example-1
User Johnnyutts
by
4.8k points

1 Answer

2 votes

Answer:

(x - 2)² + (y - 6)² = 4

Explanation:

Equation of a circle is given by,

(x - h)² + (y - k)² = r²

Here, (h, k) is the center of the circle

r = Radius of the circle,

From the graph attached,

Center of the circle → (2, 6)

Radius of the circle = 2 units

Therefore, equation of the circle will be,

(x - 2)² + (y - 6)² = 2²

(x - 2)² + (y - 6)² = 4

User Cocoatomo
by
4.8k points